Analisis Potensi Dampak Sosial dalam Restrukturisasi BUMN: Studi Kasus PT Pengembangan Armada Niaga Nasional (Persero) - Milla Marlina Assegaf; Santy Sriharyati; Hana Rengganawati; Dewi Reniawaty (POLITEKNIK LP3I, 2026)
This study analyzes the potential social impacts of the restructuring of a state-owned enterprise, focusing on PT Pengembangan Armada Niaga Nasional (PT PANN). The research applies a qualitative case study approach using the Social Impact Assessment framework to examine the effects of corporate restructuring on employees, stakeholders, and the surrounding community. Data were collected through in-depth interviews, focus group discussions, documentation review, and field observation. The findings indicate that the social impacts of the restructuring are relatively limited and concentrated on internal employees, particularly in the form of psychological uncertainty regarding job continuity. Administratively, the company has fulfilled its obligations related to wages and social security, reducing the risk of industrial conflict. Indirect impacts are observed in the local micro-economy surrounding the company, although they remain manageable. The study highlights the importance of integrating social impact analysis into restructuring policies to ensure organizational legitimacy and stakeholder stability. Workforce transition programs, transparent communication, and social protection mechanisms are recommended as key mitigation strategies. This case demonstrates that restructuring in state-owned enterprises requires not only financial considerations but also a socially responsive management approach to minimize adverse effects.